Diet Impact on the Development and Survival of Oiceoptoma thoracicum (Coleoptera: Silphidae) - Qubaiová, Jarin; Jakubec, Pavel; Montoya-Molina, Santiago; Novák, Martin; Šuláková, Hana (Journal of medical entomology, 2022)
We assessed the influence of diet on the development and survival in the immature stages of the necrophagous beetle Oiceoptoma thoracicum (Linnaeus, 1758). The species is frequently observed on large cadavers, including humans, and thus can be of potential forensic relevance. We compared multiple meat tissues from three animal sources, and detected the optimal diet for rearing the species for further entomological and forensic objectives. We reared 203 individuals to adulthood at the constant temperature of 20°C. Our results represent the first robust data set of the development time for this species. They further confirmed a significant relationship between survival and the type of diet, as the highest survival rates were detected in larvae fed with both pork liver and pork muscle.
Keywords: brouci; dieta; nutritional ecology; maso; Entomology; larval instar; zvířata; Humans; Coleoptera; Carrion beetle; Meat; larva; Larva; development time; Diet; entomologie; mortality; lidé; Animals